Association between fibromyalgia syndrome and MTHFR C677T genotype in Turkish patients - Dundar Ahi, Emine; Ikbali Afsar, Sevgi; Sözay, Seyhan; Yalçın, Yaprak; Baysan Çebi, Hatice Pınar (Journal of Surgery and Medicine, 2020)
Aim: Fibromyalgia syndrome (FMS) is characterized by widespread musculoskeletal pain and tender points. Among the several suggested mechanisms, most reports strongly emphasize the importance of the molecular mechanisms. It is known that the disorder is accompanied by various mental disorders, the most common being depression. Methylenetetrahydrofolate reductase (MTHFR) gene polymorphism was also associated with psychiatric disorders such as depression, anxiety, bipolar disorder and schizophrenia. This study aimed to evaluate the association between C677T genotype of methylenetetrahydrofolate reductase (MTHFR) gene, FMS risk and symptom severity in Turkish patients. Methods: One hundred (n=100) patients with FMS diagnosed according to the 1990 American College of Rheumatology Classification Criteria were included in our case-control study. Control group consisted of 100 patients of similar age and gender. Genomic DNA was extracted from peripheral blood leukocytes obtained from the participants and MTHFR C677T mutation was detected with real-time polymerase chain reaction. FMS disease activity was evaluated by Fibromyalgia Impact Questionnaire (FIQ) and presence of depression was assessed by Beck Depression Inventory (BDI). Results: The study and control groups were all female. Depression was detected in 42% of the study group. Results of statistical evaluation have shown that those who carry the 677 C allele are 2.111 times more likely to have FMS than those with the T allele of MTHFR (P<0.001). There was no relationship between distribution in the MTHFR gene C677 polymorphisms, functional status (P=0.107), or BDI scores (P=0.848) in study group. Conclusion: Our study found that the presence of the MTHFR C677T variant was protective against FMS. Based on these results, comprehensive studies in rare types of polymorphisms of MTHFR should be conducted.